Android based information system for eco-site destination. Issue 1 (January 2021) - Fardiansyah,; Ihsan, MA; Junanda, SF; Asmaidi,; Rahmanizar, C; Rusnanda, R; Kartawijaya, M; Candra, R A
Abstract: With the rapid development of information and communication technology, the internet has become an essential medium for obtaining or exchanging information without the obstruction of distance, time, and place. The purpose of developing this application is to design the nearest Tourism Location Search Application in South Aceh district based on Android. This application was created using Android Studio. This application provides information about existing tourist objects from location information, facilities, and guidance to reach the location using the Maps method. Users of the application can choose attractions based on categories and the system will provide a guide to the tourist sites that can be visited.